PENGARUH KESULITAN ANGGARAN TERHADAP KINERJA MANAJERIAL SEKTOR PUBLIK DAN PARTISIPASI PENGANGGARAN SEBAGAI VARIABEL MODERASI - Yusri Hazmi; Zuarni ' (Program Studi Pendidikan Ekonomi Universitas Riau, 2013)
Good governance can be defined as an organization responsible for themanagement of development by promoting the principles of democracy, efficient,efetifitas and prevention of corruption both political and administrative, run fiscaldiscipline and creating legal and political framework for the growth of businessactivities.This study aimed to determine the effect of budget difficulties on theperformance of public sector managerial, budgetary participation as a moderatingvariable. This study took the object at 5 universities in the province of Aceh. Thecollege is Kuala University, IAIN Ar-Raniry, University of Serambi Mekkah,University Muhammadiyah and the University Abulyatama. Based on the analysis,this study proves that participation in budget preparation and significant positiveeffect on managerial performance. Overall shown by the results significance valueless than 0.05. The higher participation budgeting in an organization, the highermanagerial performance. Similarly, the higher the budget will lower the level ofdifficulty on managerial performance. However, with the participation ofpengangaran as moderating variables have affected the relationship between theperformances of the budget difficulties. Variable active participation of budgeting andmanagerial performance boost.The results of this study as well as support the aimsof the budget will reduce the difficulty of managerial performance. However, with theactive participation of budgeting influence performance improvement.Keywords: Difficulty budget, budgetary participation and managerial performance.